Understanding adult survivors of childhood cancers: An analysis of a survivorship transitions clinic. Issue 28 (1st October 2022) - Hentzen, Stijn; Alsman, Kyla; O'Neal, Alicia; Adams, Taylor; Calhoun, Elizabeth; Lowry, Becky N.
Abstract : 227 Background: As the prevalence of patients with cancer increases and improvements to treatment continue, the population of childhood cancer survivors (CCS) will see remarkable growth in coming years. Care for CCS requires collaboration between oncologists and primary care practitioners (PCPs). Long term follow up calls for unique attention to survivorship guidelines, the late effects of treatment, and the risk of secondary malignancies. To meet these needs, the cancer center at the University of Kansas Health System partnered with internal medicine to establish a primary care based STC. This study aimed to describe and analyze the population of cancer survivors in this clinic. Methods: After obtaining IRB approval, a retrospective chart review was completed for patients established in the STC between 2014 and 2022. Subjects were de-identified and analysis was performed using Microsoft Excel. Results: The 261 patients were 57% (150) female and had an average age of 12 (2 months - 41 years) at the time of cancer diagnosis and an average age of 28 (18 – 61 years) at the time of of clinic establishment. Patients were from 9 states, 47 counties, and 139 unique zipcodes. We identified 42 different cancers among the patients with ALL (24.5%) and Hodgkin's Lymphoma (19.2%) most common. We found that 244 (93.5%) received chemotherapy, 138 (52.9%) received radiation, and 41 (15.7%) underwent bone marrow transplant. Secondary cancers were diagnosed in 30 (11.5%) of the patients with breast (23.3%) and thyroid (23.3%) malignancies most common. Three of these patients had two secondary malignancies. Conclusions: Our CCS population was clinically diverse in malignancy and treatment regimen. Nearly half of the patients received therapy in combination, adding to the complexity of late effects risks and care monitoring. This is emphasized by the prevalence of secondary malignancies which enforces the need for close follow up and adherence to survivorship guidelines. We found that despite the young age of cancer diagnosis, many of the patients established care in our clinic well into adulthood which is concerning for a gap in survivorship care as patients transition from treatment to follow up. Finally, the wide catchment area of this clinic is unique and shows the success of rural survivorship care at a tertiary medical center.